2011
DOI: 10.1002/ejlt.201100075
|View full text |Cite
|
Sign up to set email alerts
|

Performance of palm‐based fat blends with a low saturated fat content in puff pastry

Abstract: Four fat blends based on palm fractions in combination with high oleic sunflower oil (HOSF) with a relatively low saturated fatty acid content (29.2 AE 0.85%, i.e. less than 50% of that of butter) were prepared. The saturated fat was located in different TAG structures in each blend. Principal saturated TAG were derived from palm stearin (POs, containing tripalmitoyl glycerol-PPP), palm mid-fraction (PMF, containing 1,3-dipalmitoyl-2-oleoyl glycerol-POP) and interesterified PMF (inPMF, containing PPP, POP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…This is in accordance with the findings of Garcia-Macias et al (2011, who reported a lower lift for puff pastry produced with vegetable roll-in fats compared to puff pastry containing butter (66 % SAFA). These studies used FBs which contained about 30 % SAFA, namely palmitic acid (Garcia-Macias et al 2011) and stearic acid, respectively (Garcia-Macias et al 2012).…”
Section: Puff Pastry Qualitysupporting
confidence: 92%
See 3 more Smart Citations
“…This is in accordance with the findings of Garcia-Macias et al (2011, who reported a lower lift for puff pastry produced with vegetable roll-in fats compared to puff pastry containing butter (66 % SAFA). These studies used FBs which contained about 30 % SAFA, namely palmitic acid (Garcia-Macias et al 2011) and stearic acid, respectively (Garcia-Macias et al 2012).…”
Section: Puff Pastry Qualitysupporting
confidence: 92%
“…These peaks are indicative of the high levels of higher-melting triacylglycerides (TAGs, e.g. tripalmitin) (Siew et al 2007;Garcia-Macias et al 2011). With increasing amounts of PS the endothermic curve had an observable shoulder occurring at a lower temperature than the main peak (Fig.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Fat plasticity, consistency and melting properties are some of the key performance characteristics for roll-in fat (Pajin et al, 2011). Fat functionality during pastry production has been studied (Garcia-Macias et al, 2011;Pajin et al, 2011;Bousquieres et al, 2014) and reviewed (Wickramarachchi et al, 2015;Ooms et al, 2016) elsewhere.…”
Section: Introductionmentioning
confidence: 99%